2012
DOI: 10.1021/jp300904p
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical Trajectory Dynamics Study of Atomic Oxygen Collisions on an O-Preadsorbed Graphite (0001) Surface with a New Analytical Potential Energy Surface

Abstract: A new flexible periodic LEPS potential energy surface (FPLEPS) based on density functional theory data is constructed for the interaction of atomic oxygen with an O-preadsorbed graphite (0001) surface over a C−C bridge. New ingredients were added to the usual expression of the FPLEPS in order to take into account the entrance barriers, molecular orientation, and morphology of the surface. A total of 563 DFT points were used to fit the Eley−Rideal (ER) reaction channel, achieving a root-mean-square deviation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 64 publications
5
35
0
Order By: Relevance
“…Periodic density functional theory calculations have been performed using the Vienna ab initio simulation package (VASP) 11,12,13,14 . All the details about the methodology used (e.g., GGA/RPBE functional, energy cut off, slab model, …) were discussed deeply in previous works 8,9,10 devoted to atomic oxygen interaction with both a clean and an O-preadsorbed graphite surfaces, and are omitted here. New DFT calculations have been performed in order to check the accuracy of the analytical FPLEPS PES in describing the O2/graphite interaction.…”
Section: B Dft Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodic density functional theory calculations have been performed using the Vienna ab initio simulation package (VASP) 11,12,13,14 . All the details about the methodology used (e.g., GGA/RPBE functional, energy cut off, slab model, …) were discussed deeply in previous works 8,9,10 devoted to atomic oxygen interaction with both a clean and an O-preadsorbed graphite surfaces, and are omitted here. New DFT calculations have been performed in order to check the accuracy of the analytical FPLEPS PES in describing the O2/graphite interaction.…”
Section: B Dft Calculationsmentioning
confidence: 99%
“…In the case of a hyperthermal O beam colliding with a clean graphite surface, the QCT 9 and the experimental 5 distributions practically matched the maximum position (θv' = 65° and 62°, respectively) and also the distribution shape. Moreover, O2 molecules formed by Eley-Rideal reaction were also calculated by using QCT at the same hyperthermal atomic conditions 10 . These Eley-Rideal formed O2 molecules could contribute to the final experimental observed O2 polar scattering angular distribution together with the reflected O2 molecules.…”
Section: B Hyperthermal Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy released in the reaction can be shared among the degrees of freedom of the newly formed molecules (rotations, vibrations, translation and, possibly, electronic) and the degrees of freedom of the substrate (phonons and, possibly, electrons). Different systems of interest in aerospace applications have been investigated using Molecular Dynamics (MD) studies by means of classical or quasi-classical trajectories [72,73,74] and semiclassical methods [75,76,77,78,79,80,81,82], by deriving the probability of recombination and the ro-vibrational nascent distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Density Functional Theory (DFT) based modelling has been shown its capability of providing such detailed physical and chemical information during the interactions between carbon element and energetic atomic/molecular oxygen. Studies on the interaction between graphite surface and high-energy oxygen atoms [14][15][16][17] reported that oxygen molecules were generated during the collisions due to the surface catalysis effect through the Eley-Rideal (E-R) mechanism, which was much more important than the Langmuir-Hinshelwood (L-H) mechanism. The formation mechanism of CO and CO2 was further investigated with DFT method by Paci et al [18][19][20][21], reporting that oxygen atoms were adsorbed on the graphite surface to form epoxy functional groups firstly, which were then diffused to form ketone groups or carbonyl groups, resulting different formation of CO and CO2.…”
Section: Introductionmentioning
confidence: 99%